Beispiel Nr: 05
$ \text{Gegeben: } \text{ Punkt } A(xa/ya) \qquad \text{ Scheitel } S(xs /ys) \\ \text{Gesucht:} \\ y=ax^{2}+bx+c \\ \\ \text{Scheitel und Punkt}\\ \textbf{Gegeben:} \\ A(-\frac{1}{2}/2)\qquad \text{ Scheitel } S(6/0) \\\\ \\ \textbf{Rechnung:} \\ A(-\frac{1}{2}/2)\qquad S(6/0) \\ \text{Punkt A und Scheitel S in die Scheitelform einsetzen}\\ y=a(x-xs)^2+ys \\ 2=a(-\frac{1}{2}-6)^2+0 \\ 2=42\frac{1}{4}\cdot a+0 \qquad /-0 \qquad /:42\frac{1}{4} \\ a=\frac{2-0}{42\frac{1}{4}} \\ a=0,0473 \\ y=0,0473(x-6)^2+0 \\ y=0,0473(x^2 -12 x+6^2)+0 \\ y= 0,0473x^2-0,568x+1,7 $